Exploring the effects of pillow talk on relationship satisfaction and physiological stress responses to couples' difficult conversations. Issue 3 (2nd July 2020) - Denes, Amanda; Crowley, John P.; Winkler, Kara L.; Dhillon, Anuraj; Ponivas, Ambyre L. P.; Bennett, Margaret
ABSTRACT: This study examined the effects of pillow talk (i.e., communication after sexual activity) on relationship satisfaction and physiological stress responses to difficult conversations. Fifty heterosexual couples were randomly assigned to either a pillow talk condition in which they doubled their pillow talk for three weeks or a control condition. After three weeks, participants came to the lab to engage in a conflict conversation. Saliva samples taken before and after the conversation were assayed for cortisol, a physiological marker of stress. The results indicate that increased pillow talk produces greater relationship satisfaction for men (but not women), but does not benefit either group's physiological stress responses. The findings suggest that pillow talk has distinct benefits for romantic relationships.